Phytochemical properties and antioxidant activities of the leaf extracts of Boenninghausenia albiflora (Hook.) Rchb. ex. Meisn. (Rutaceae) - I Putu Agus Hendra Wibawa; Putri Sri Andila; Vienna Saraswaty; I Gede Tirta (The East Java Biological Society, 2020)
Boenninghausenia albiflora is a well-known plant for being used in various traditional treatments. The plant is also reported to contain an essential oil which has a distinctive and pungent aroma. The present study aimed at investigating extraction yields, phytochemical compounds and antioxidants, and potential uses of B. albiflora leaves extracted with acetone solvent. Bioactive compounds of the leaf extract of B. albiflora were identified by GC-MS analysis while the antioxidant assay was measured by DPPH method. The extract obtained from acetone contained 30 compounds including coumarin group, 2-Isoprenyl-2,3-dihydro-furo [3,2-G] chromen-7-one (22.89% w/v) as the highest percentage compound. Other coumarins such as suberosin and dehydrogeijerin were also identified in this study. The IC50 values of the leaves extract of B. albiflora was 194.3 ppm which was higher than propyl gallate. Thus indicating B. albiflora as potential sources of anti-cancer, anti-inflammatory and antioxidant.